Uptake and accumulation rate of arsenic by blyxxa malayana - Cynthia Rawlin, anak Roney. (Universiti Malaysia Sarawak, (UNIMAS), 2004)
This study was carried out to determine the accumulation rate of arsenic by Blyxxa malayana and also to assess the potential of this plant as bio-indicator. The Blyxxa malayana was transplanted in different arsenic concentrations solution ; no arsenic contains 0.2 ppm arsenic, 0.6 ppm arsenic and 1.2 ppm arsenic. The concentration of arsenic in Blyxxa malayana, soil sample and water sample was analyzed every 2 weeks for 8 weeks using Voltammetry (757 VA Computrace). The results indicated that there are relationships between the amount of arsenic accumulated by Blyxxa malayana to the arsenic soil concentration and arsenic solution concentration. There are increasing in amount of arsenic accumulated in Blyxxa malayana due to the increasing arsenic soil and arsenic solution concentration. Overall, Blyxxa malayana was a plant with potential arsenic accumulator properties and it can be applied as bio-indicator for the arsenic contaminated condition.